Reduction of Huntington’s Disease RNA Foci by CAG Repeat-Targeting Reagents - Urbanek, Martyna O.; Fiszer, Agnieszka; Krzyzosiak, Wlodzimierz J. (Frontiers in Cellular Neuroscience, 2017)
In several human polyglutamine diseases caused by expansions of CAG repeats in the coding sequence of single genes, mutant transcripts are detained in nuclear RNA foci. In polyglutamine disorders, unlike other repeat-associated diseases, both RNA and proteins exert pathogenic effects; therefore, decreases of both RNA and protein toxicity need to be addressed in proposed treatments. A variety of oligonucleotide-based therapeutic approaches have been developed for polyglutamine diseases, but concomitant assays for RNA foci reduction are lacking. Here, we show that various types of oligonucleotide-based reagents affect RNA foci number in Huntington's disease cells. We analyzed the effects of reagents targeting either CAG repeat tracts or specific HTT sequences in fibroblasts derived from patients. We tested reagents that either acted as translation blockers or triggered mRNA degradation via the RNA interference pathway or RNase H activation. We also analyzed the effect of chemical modifications of CAG repeat-targeting siRNAs on their efficiency in the foci decline. Our results suggest that the decrease of RNA foci number may be considered as a readout of treatment outcomes for oligonucleotide reagents.